Rationale for the use of electrophoresis of drugs in post-stroke patients with visual impairments: a review - Detelina B. Kulchitskaya; Tatiana V. Konchugova; Tatyana V. Marfina; Tatiana V. Apkhanova (Вестник восстановительной медицины)
INTRODUCTION. Disorders of vision and oculomotor functions are widespread among patients who have suffered a cerebral stroke. The rehabilitation system for patients who have suffered a stroke makes use of physiotherapy methods that can significantly improve haemodynamic processes and regeneration. Among the best-known physiotherapeutic methods is drug electrophoresis.